2013
DOI: 10.1152/japplphysiol.01107.2012
|View full text |Cite
|
Sign up to set email alerts
|

New records in aerobic power among octogenarian lifelong endurance athletes

Abstract: We examined whole body aerobic capacity and myocellular markers of oxidative metabolism in lifelong endurance athletes [n = 9, 81 ± 1 yr, 68 ± 3 kg, body mass index (BMI) = 23 ± 1 kg/m(2)] and age-matched, healthy, untrained men (n = 6; 82 ± 1 y, 77 ± 5 kg, BMI = 26 ± 1 kg/m(2)). The endurance athletes were cross-country skiers, including a former Olympic champion and several national/regional champions, with a history of aerobic exercise and participation in endurance events throughout their lives. Each subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 59 publications
5
53
2
1
Order By: Relevance
“…2). Although HR max has been documented to be higher in master athletes compared to agematched untrained controls (Trappe et al 2013), a lower HR max with age seems to be inevitable and has previously been suggested to be a significant factor likely, somewhat, responsible for the fall in VO 2max (Heath et al 1981). In the current study the pre-training data were in agreement with the expected decline in HR max with age and a subsequent increase in SV max , resulting in an unchanged Q max .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2). Although HR max has been documented to be higher in master athletes compared to agematched untrained controls (Trappe et al 2013), a lower HR max with age seems to be inevitable and has previously been suggested to be a significant factor likely, somewhat, responsible for the fall in VO 2max (Heath et al 1981). In the current study the pre-training data were in agreement with the expected decline in HR max with age and a subsequent increase in SV max , resulting in an unchanged Q max .…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it has been documented that old subjects can both maintain a high VO 2max and achieve significant improvements in aerobic capacity with endurance training (Grimsmo et al 2010;Hagberg et al 1985;Murias et al 2010;Osteras et al 2005;Tanaka and Seals 2008;Trappe et al 2013). However, attempts to examine the effect of age on the plasticity of VO 2max have been clouded by anomalies either in study design or analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…E2). Two studies showing positive effect estimates for COPD were selective in their study design; in the case of the EX-ATHLETES study, the positive effect of lifetime physical exercise on biological age may have played a role [3,27,46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, even if recreational masters athletes had relatively short training histories and little experience in triathlon, these successful athletes probably have lifelong histories of physical activity. [110,111,112,113] …”
Section: Improvements In Triathlon Performance Of Elderly Triathletesmentioning
confidence: 99%